PROFESSIONAL DISEASE OF WORKERS OF THE AIRCRAFT PLANT OF ULAN-UDE - S. V. Tsyrempilov (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
In the article the analysis of professional disease of workers of Aircraft plant of Ulan-Ude is presented.